Sales Administration Information System and Management of Expired Products in Prosperous Grocery Stores - Muhammad Syaiful Ulum; Lukman Junaedi; Achmad Zakki Falani (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Grocery stores play a vital role in fulfilling people's basic needs, especially in urban and rural areas. However, in operational practice, grocery stores still often face classic obstacles such as inefficient sales management and difficulties in controlling stock items that are prone to expiration. With the support of increasingly sophisticated technology as it is today, information systems are an additional tool that can be used by businesses to market their goods and services online. This research aims to design and develop a website-based sales administration and expired product management information system, which can help problems in grocery stores. The system development method uses the Waterfall method, while the research uses qualitative methods with data collection techniques through interviews, observations and literature studies. The system is built using PHP, Laravel, MySQL, Javascript Bootstrap and applies the FIFO algorithm in managing stock items and system testing using Black Box Testing.